Humanizing the City. Raul Lino the portuguese circumstance(s) and the case of Lisbon - Pereira, Paulo Manta (Staged Nature, 2020)
Over a period of nearly one hundred years, Raul Lino (1879-1974) experienced the profound political, social and economic changes that marked the twentieth century in Portugal, between the constitutional monarchy and the three republics mediated by the four-decade political dictatorship of the Estado Novo (New State). He was the most published architect in Portugal, having become known for the controversial defense of the Campanha da casa Portuguesa (Portuguese House Campaign), that had its peak after the inauguration of the retrospective exhibition on his work at the Calouste Gulbenkian Foundation in 1970. He is less known for the quality of his transversal synthesis conceived between urbanism, architecture, the decorative arts, and its underlying affirmation of an idea of the city, that we conjecture from his narrative focused on the city of Lisbon as a liberal professional (1900-1934) or public servant (1934-1949) in the triple representation of his role as thinker, author and evaluator. Quoting Aristotle, Raul Lino conceived the city as the locus of happiness, shaping forms of consensus between tradition and modernity by means of an architecture at the scale of man and in proportion to his circumstance, consistently outlining a modern possibility of continuity.